FOOD SECURITY APPROACH: SYSTEMATIC LITERATURE REVIEW ON DIVERSIFICATION, ACCESS, AND STABILITY IN AGRICULTURAL FOOD SUPPLY - Era Purike; Entin Solihah (ADISAM Publisher, 2025)
Food security is a crucial issue in ensuring sufficient, nutritious, and sustainable food availability for the community. This study systematically reviews the literature on food security approaches, focusing on three main dimensions: diversification, access, and stability in agricultural food supply. Through a systematic literature review, this study filters and analyses various reliable scientific sources to gain a comprehensive understanding of the roles and challenges of these three aspects in the context of food security. The results of the study show that food diversification contributes significantly to improving the sustainability of the food system and nutritional quality, while adequate food access and supply stability are key to ensuring food affordability and continuity for all levels of society. These findings emphasise the need for an integrated approach that combines production diversification, strengthening socio-economic access, and policies that support supply stability to effectively improve national and global food security. This study provides a strong scientific basis for the development of policy strategies and agricultural practices that are more adaptive and inclusive of environmental and socio-economic changes.